Impact of eggshell membrane on metabolism and cell adhesion in oxidatively stressed canine chondrocytes - Juraj Vozar; Nikola Hudakova; Natalia Nosalova; Mykhailo Huniadi; Dana Marcincakova; Slavomir Hornak; Lubica Hornakova; Petra Majerova; Dasa Cizkova; Dasa Cizkova (Frontiers in Veterinary Science)
Eggshell membrane (ESM) is a rich source of bioactive compounds, including proteins, peptides, and antioxidants, contributing to its potential therapeutic benefits. These natural antioxidants might help neutralize reactive oxygen species (ROS) and modulate inflammatory responses, which are often linked with chondrocyte damage in osteoarthritis. In this study, we investigated the functional effects of ESM proteins on H2O2-induced oxidative stress in a neonatal canine chondrocytes. The isolated neonatal chondrocytes demonstrated a high proliferation rate and increased glycosaminoglycan (GAG) production during cultivation. In addition, the expression of key cartilage markers, including collagen types II and IX, and aggrecan, confirmed the retention of the chondrocyte phenotype. Under in vitro conditions, post-treatment with ESM improved chondrocyte viability, indicating that ESM may have a reparative role in mitigating oxidative damage. This significant therapeutic potential was validated through XTT assays, which measured cell metabolic activity at 24 h, and Real-time Cell Analysis (RTCA), providing continuous monitoring over 98 h. In contrast, the preventive effects of ESM against stress were observed exclusively in the XTT analysis. By investigating these aspects, we provide insight into the potential of ESM proteins to protect chondrocytes from oxidative damage, particularly in cartilage repair and joint health. This study is one of the first to create a vital platform based on canine neonatal chondrocytes for monitoring dietary supplements designed to prevent or repair dog cartilage damage. Thus, the study offers a valuable contribution to understanding how ESM bioactive compounds can be used therapeutically, bridging the gap between in vitro findings and practical applications in veterinary medicine.